2022
DOI: 10.1093/cdn/nzac061.089
|View full text |Cite
|
Sign up to set email alerts
|

Pregnant Women’s Experience With Multiple Micronutrient Supplements (MMS): Qualitative Research From Three Districts in Indonesia

Abstract: Objectives The provision of multiple micronutrient supplements (MMS) to pregnant women is efficacious in improving pregnancy outcomes, safe, cost-effective, and recommended in the context of rigorous research by the World Health Organization. This study examines experiences related to MMS adherence in Indonesia. Methods Qualitative methods were used and included focus group discussions (FGD) with 52 pregnant women who receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Contrarily, roundshaped tablets are the most difficult to swallow, despite coating efforts to make the swallowing process easier 30 . Based on research conducted by Thaha (2022), mothers consume MMS because of its shape and size, which make it easy for them to swallow 31 . Therefore, it could be concluded that MMS in capsule form had a higher acceptance rate because the capsule membrane may lessen any unpleasant feelings that may appear when consuming the supplement and make it easier to swallow.…”
Section: Factors Associated With the Consumption Adherence Of Ifa And...mentioning
confidence: 99%
“…Contrarily, roundshaped tablets are the most difficult to swallow, despite coating efforts to make the swallowing process easier 30 . Based on research conducted by Thaha (2022), mothers consume MMS because of its shape and size, which make it easy for them to swallow 31 . Therefore, it could be concluded that MMS in capsule form had a higher acceptance rate because the capsule membrane may lessen any unpleasant feelings that may appear when consuming the supplement and make it easier to swallow.…”
Section: Factors Associated With the Consumption Adherence Of Ifa And...mentioning
confidence: 99%